Media in the Crisis and the Crisis in Media - Todorov, Petko (UNWE Yearbook, 2011)
The text is dedicated to some of the major dimensions of the world economic crisis and its influences and reflections on the Bulgarian media market. The media in crisis and the crisis in the media are connected concepts that are worth being analyzed and evaluated because on their condition depends the finding of the “communication key” for resolving the social and economic problems. Here some of the essential problems in the Bulgarian media sphere will be analyzed. Problems that received new dynamics under the conditions of an economic and financial crisis. How the crisis is changing the contents and the economic character of media? What is the profile and the dynamics of periodic press in contemporary Bulgaria? What reasons define the market dispositions of the press? What determines the spiral “print run – advertising” and is it possible to talk about editorial independence? How did the crisis become a catalyst of merging and a concentration of capital in the media sector? On what stage of its development is the advertising and more specifically in the context of contents and the survival of media in a crisis situation? Which are the necessary steps and innovative decisions for overwhelming the crisis effects in the social influence and economic condition of Bulgarian  media?The study is trying to answer these and many other important issues of contemporary Bulgarian media sphere.